Evaluation On Polar Quassinoids Of Eurycoma Longifolia Jack As Potential Anti-benign Prostatic Hyperplasia Agents - Viji, Mathias Mathew Hipolith (2024)
The quassinoids of Eurycoma longifolia Jack have shown promising antiproliferative activity against prostate cancer cells. This study hypothesized that this class of compounds would also be active against benign prostate hyperplastic (BPH) cells. Hence, this thesis aimed firstly, to isolate known and novel quassinoids by systematic fractionation of the polar fraction of the plant, and secondly, to determine the activity of the quassinoids as potential anti-benign prostate hyperplasia agents, in vitro and in vivo. Systematic fractionation of 70% alcoholic extract of E. longifolia roots through Diaion HP20 resin column produced four major fractions TAF1(10% Methanol in water), TAF2(30% Methanol in water), TAF3(50% Methanol in water), and TAF4(100% Methanol in water), in decreasing order of polarity. The second most polar fraction TAF2, found to contain a majority of the targeted quassinoids, was further pursued through a series of fractionation and purification steps, resulting in the isolation of nine known quassinoids and three hitherto unreported compounds: 71, a picrasinolide-type C19 quassinoid; 72, a C20 quassinoid glycoside; and 73, a C20 quassinoid. The structures of the compounds were confirmed and their configurations assigned by an array of spectroscopic techniques. The twelve quassinoids were evaluated in vitro in a benign prostate hyperplasia cell line BPH-1 for their ability to inhibit cell growth.